A study of consumer awareness about products and services offered by Tabung Haji Johor Bahru / Noraini Abdul Manan - Abdul Manan, Noraini (2007)
Tabung Haji is known as Islamic Institution that provides Haj for Muslims. The study discusses the consumer awareness about the product and services offered by THJB through brand name, promotion, consumer knowledge and the auxiliary services as independent variables of the case study. Respondents were derived from THJB customers who are living in the Johor Bahru area. 180 questionnaires are distributed to 180 respondents. This research uses convenience sampling, in which respondents are randomly selected and the sample size of 180, is only 6 percent of 3000 customers of TH. This study applies frequencies and Chi Square Test and the results were expressed in percentage terms exhibited in the forms of tables, charts and graph. The impact for this study could benefit the organization as well as the customers. It shows that consumers were not aware of the product offered by THJB and they also are not aware of the auxiliary services of THJB because of several factors. Thus some initiatives need to be taken to increase the level of awareness of consumer in particular through varies of promotion and strategies.